The Effect of Financial Literacy, Financial Attitude, and Income on Personal Financial Management Behavior Among Millennials in Lhokseumawe City - Koko Bustami; Najwa Fauziah; Rina Oktaviany; Murni Murni (Journal of Social Research, 2025)
This study examines the influence of financial literacy, financial attitude, and income on the personal financial management behavior of millennials in Lhokseumawe City. As a productive demographic, millennials face significant economic pressures, making effective financial management crucial. This study aims to determine the influence of financial literacy, financial attitude, and income on personal financial management behavior of the millennial generation in Lhokseumawe City. The population in this study consisted of all millennial generations in Lhokseumawe City aged between 29 and 44 years, totaling 47,732 people. The approach used in this study was quantitative, employing a survey method by distributing questionnaires to 100 respondents selected through simple random sampling techniques. Data analysis was carried out using multiple linear regression to test the partial and simultaneous effects of the independent variables on the dependent variable. The results of the study indicate that, partially, financial attitude has a significant effect on personal financial management behavior, while financial literacy and income do not have a significant partial effect. However, simultaneously, the three variables have a significant effect on the personal financial management behavior of the millennial generation in Lhokseumawe City. This study implies that increasing positive financial attitudes plays an important role in forming healthy financial behavior. In addition, although financial literacy and income do not have a direct effect, it remains necessary to increase financial awareness and understanding in the younger generation.